The sound of science: a sonification learning experience in an Italian secondary school - Eramo, Giacomo; Pastore, Serafina; De Tullio, Mario; Rossini, Valeria; Monno, Alessandro; Mesto, Ernesto (Frontiers in Education, 2025)
IntroductionThe present article reports on a case study aimed at improving STEAM education in secondary schools. It discusses the use of sonification as a teaching strategy to integrate music into science learning, using different approaches from data audification to parameter mapping into aural models and to the rewriting of song lyrics based on STEM topics.MethodsA qualitative research study has been performed in a secondary school in the school district of Bari (South of Italy). More specifically, students’ and experts’ perceptions of experienced sonification activities have been collected through six rounds of focus group interviews.ResultsWhile there was a good improvement in student achievement in science, it is worth noting how musical activities also led to some benefits for students involved in the sonification workshops. The integration of music with STEM disciplines has promoted more cooperation and empathy among the students. Additionally, musical inputs can help students discover and regain interest in music. However, the study also highlighted the differences in teacher training and content knowledge, suggesting the need for future research to consider broader samples and experimental designs.DiscussionResults and implications for educational research and practice are discussed considering the recent literature on STEAM. Finally, this study demonstrates the importance of a robust instructional design for sonification activities, so that they can be more effective, aligned with the school curriculum, and integrated into the classroom teaching-learning process.